Willingness to Study, Self-Efficacy and Causal Attributions in Chilean University Students - Sáez, Fabiola M. (2018)
The aim of this study is to analyze the relationship between (1) willingness to study strategies, (2) causal attributions (to effort, ability and external causes) and (3) student´s perception of self-efficacy about their ability to self-regulate their processes of willingness to study. Method: An instrument built by the researchers called Willingness to the Study Self-Regulation Questionnaire was applied to a non probabilistic convenience sample of 695 Chilean university students from 5 universities of the Province of Concepción. Outcomes: Strong correlations were found between selfefficacy for the willingness to study self-regulation and the willingness to study strategies (r=0.54 to r =0.55). the willingness to study strategies had positive and moderate correlations (r=0.38 to r=0.42) with causal attributions for success to effort, weak correlations (r=0.15 to r=0.28) with causal attributions for success to ability and to external factors, and negative weak to moderate correlations (r=-0.19 to r =-0.38) with causal attributions for failure to effort, ability, and external factors. Conclusions: Students with high levels of willingness to study strategies show positive beliefs about their own ability to self-regulate their processes of willingness to study, they make causal attributions for their success mainly to effort, and they attribute their academic failure less and less to ability and external factors.